Evaluation of the efficacy of a new hyaluronic acid gel on dynamic and static wrinkles in volunteers with moderate aging/photoaging - Sparavigna, Adele (Clin Cosmet Investig Dermatol, 2019)
PURPOSE: Aim of the study was to determine both clinically and by noninvasive instrumental evaluations the efficacy, tolerability and the duration of the effects of a new hyaluronic acid (HA) gel in human volunteers with moderate aging/photoaging. PATIENTS AND METHODS: Eighteen volunteers (35–55 years) were enrolled in this single-center study. The subjects underwent five visits. The first visit was at baseline to determine the adherence to the inclusion criteria, followed by the first injection of the HA-based study product, and the second visit was at 48 hours after the injection. Two months later, a second injection was given (Visit 3) followed by a subsequent visit (Visit 4) after 48 hours. The last visit (Visit 5) was performed 5 months after the first injection. Clinical and instrumental evaluations as well as self-assessment by the subjects were recorded at each visit. RESULTS: A significant improvement of wrinkles’ grade around the eyes, vertical lip lines and wrinkles’ severity of nasolabial folds was recorded after the first injection and the effect increased after the second injection. Aging/photoaging grade and surface microrelief improved 2 months after the first injection procedure. These clinical improvements were paralleled by amelioration of instrumental skin profilometry and optical colorimetry. The treatments were very well tolerated by the volunteers as determined by the self-grading score. CONCLUSION: The results confirm the good esthetic performance and the duration of the effect of the HA-based study product (Viscoderm(®) Hydrobooster) on dynamic facial wrinkles and/or static facial lines. These effects were particularly evident after the second injection and were accompanied by a good tolerability of the product.